Long-term follow-up of older patients with Mobitz type I second degree atrioventricular block. Issue 5 (19th October 2012) - Coumbe, Ann G; Naksuk, Niyada; Newell, Marc C; Somasundaram, Porur E; Benditt, David G; Adabag, Selcuk
Abstract : Objective: To examine the long-term survival of older patients with Mobitz I second degree atrioventricular (AV) block. Design: Retrospective cohort study. Propensity score adjustment for requiring a cardiac implantable electronic device (CIED) was performed. Multivariable Cox regression analysis was used. Setting: Tertiary care referral centre. Patients: We examined 299 older patients (age >45 years) with Mobitz I second degree AV block on ECG at the Minneapolis Veterans Affairs Medical Center from 1992 to 2010. Main outcome measure: Survival. Results: The average age of patients was 75±9 years; 99% were male; 59% had coronary heart disease; 44% had heart failure. 141 (47%) patients required CIED, of which 17 were implantable cardioverter-defibrillators (ICDs). CIEDs were implanted a median of 110 days after the ECG for symptomatic bradycardia, high-degree AV block or prevention of sudden cardiac death. Patients with CIED had greater cardiac co-morbidity than those without CIED. After a median 3.3 years of follow-up (range 3 days to 19 years), 190 (64%) patients died. Patients with CIED had longer survival than those without CIED (p=0.001). In propensity-adjusted multivariable Cox regression analysis, CIED implantation was associated with a 46% reduction in mortality (HR 0.54, 95% CI 0.35 to 0.82; p=0.004). Excluding 17 patients with ICDs did not alter the results. Conclusions: In this retrospective cohort study of older male patients with Mobitz I AV block on ECG, CIED implantation was associated with longer survival.